2004
DOI: 10.1021/bi048680w
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Cardiac Glycosides and Sodium/Potassium-ATPase:  Three-Dimensional Structure−Activity Relationship Models for Ligand Binding to the E2-Pi Form of the Enzyme versus Activity Inhibition

Abstract: Sodium/potassium-ATPase (Na/K-ATPase) is a transmembrane enzyme that utilizes energy gained from ATP hydrolysis to transport sodium and potassium ions across cell membranes in opposite directions against their chemical and electrical gradients. Its transport activity is effectively inhibited by cardiac glycosides, which bind to the extracellular side of the enzyme and are of significant therapeutic value in the treatment of congestive heart failure. To determine the extent to which high-affinity binding of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
107
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(120 citation statements)
references
References 48 publications
11
107
1
1
Order By: Relevance
“…Although the results between the QN mutant and the EGPLC mutant for the various analogues differ, the IC 50 values obtained with both methods (ATPase inhibition measurements and [ 3 H]ouabain replacement studies) are, in general, rather similar for a single drug used with one of both ATPases. Our findings for Na,K-ATPase (QN) contrast with those of Paula et al [26] who carried out apparently similar studies on lamb kidney ATPase (that also contains a Gln on position 111 and an Asn on position 122) with a very large series of Amino acids that were shown to be essential for ouabain binding [13,14] are indicated in yellow. Images were created with Yasara (www.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Although the results between the QN mutant and the EGPLC mutant for the various analogues differ, the IC 50 values obtained with both methods (ATPase inhibition measurements and [ 3 H]ouabain replacement studies) are, in general, rather similar for a single drug used with one of both ATPases. Our findings for Na,K-ATPase (QN) contrast with those of Paula et al [26] who carried out apparently similar studies on lamb kidney ATPase (that also contains a Gln on position 111 and an Asn on position 122) with a very large series of Amino acids that were shown to be essential for ouabain binding [13,14] are indicated in yellow. Images were created with Yasara (www.…”
Section: Discussioncontrasting
confidence: 95%
“…yasara.org) Table 2 Hydrogen bonds between Na,K-ATPase (QN) and ouabain analogues Na,K-ATPase ouabain analogues. Whereas their results on Na,K-ATPase inhibition, with exception of those for strophanthidin, fit reasonably well with our findings, Paula et al [26] found for all inhibitors, except digoxin, much higher IC 50 values in ouabain replacement studies than we found in the present study (Table 3). An explanation for this discrepancy cannot yet be given.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The amino acid sequences of the 5 external loops of the α1 isoforms of rat, sheep and X. laevis differ primarily in the 23 amino acid external loop between M1 and M2. The residues identified as determinants of cardiac glycoside binding in the sheep and human enzymes [45,46] Table 3). In the first external loop, 5 of the 23 amino acids in rat differ from sheep, 3 of which have been identified as determinants of ouabain binding.…”
Section: Progesterone Binding Sites(s) On the In Situ α1-isoformmentioning
confidence: 99%
“…In addition to its well known cardiac activity, which is mediated by inhibition of the plasma membrane Na ϩ ͞K ϩ -ATPase (17), digitoxin has demonstrated in vitro anticancer properties (18), and patient profiling suggests the survival rate of cancer patients taking digitoxin is statistically enhanced (19,20). Cardiac glycosides were also recently noted to inhibit the expression of four genes that are overexpressed in prostate cancer cells, including transcription factors and the apoptosis inhibitor survivin (21), and to provide protective effects against polyglutamine-based diseases (22).…”
mentioning
confidence: 99%